Comprehensive Overview and New Research on Carbonate Rocks of the Sé Velha Cathedral in Coimbra, Portugal - Tavares, Alice; Rocha, Fernando; Fragata, Ana; Costa, Aníbal; Oliveira, Matilde (My University, 2024)
In addition to the surrounding climatic environment, the intrinsic characteristics of the stones used in construction are a critical factor to understand a building’s conservation state and define the necessary planning and conservation management activities. The use of environmentally susceptible stones, such as carbonate stones, in heritage buildings can be especially problematic. The present investigation presents an overview of past research and contributes to identifying the types of carbonate stones used over time in Coimbra’s Old Cathedral in Portugal, which was classified as a National Monument and integrated into the Coimbra World Heritage site by UNESCO. Our mineralogical and chemical analyses revealed the use of carbonate stones from different quarries (Coimbra region), including Ançã limestone and dolostone (Porta Especiosa portal), Portunhos limestone and Outil limestone (in the perimeter of windows), and marlstones and Outil limestone (side facades). These stones, which were installed at various times during the construction and alteration of the monument, represent a great challenge for conservation planning due to their intrinsic vulnerability to adverse environmental conditions and pollution.
Keywords: Built heritage; Carbonate stone; Limestone; Dolostone; Marlstone; Porta Especiosa; Coimbra UNESCO site